A MULTI START HEURISTIC BASED ON GRASP FOR AN AUTOMATIC CLUSTERING PROBLEM - Cruz, Marcelo Dib; Ochi, Luiz Satoru (Pesquisa Operacional para o Desenvolvimento, 2015)
Clustering is the process by which elements of a database are assigned to clusters of similar elements. In clustering algorithms, it is usually assumed that the number of clusters is known. Unfortunately, the optimal number of clusters is unknown for many applications. These problems are known as Automatic Clustering Problems (ACP). In this work we present a new multi start heuristic based in GRASP for ACP including two local search operators and path relinking procedure. Computational results on a set of instances illustrate the effectiveness and the robustness of the proposed heuristic.